Neuronal release of d-serine: a physiological pathway controlling extracellular d-serine concentration - Rosenberg, Dina (The Federation of American Societies for Experimental Biology, 2010)
d-Serine is thought to be a glia-derived transmitter that activates N-methyl d-aspartate receptors (NMDARs) in the brain. Here, we investigate the pathways for d-serine release using primary cultures, brain slices, and in vivo microdialysis. In contrast with the notion that d-serine is exclusively released from astrocytes, we found that d-serine is released by neuronal depolarization both in vitro and in vivo. Veratridine (50 μM) or depolarization by 40 mM KCl elicits a significant release of endogenous d-serine from primary neuronal cultures. Controls with astrocyte cultures indicate that glial cells are insensitive to veratridine, but release d-serine mainly by the opening of volume-regulated anion channels. In cortical slices perfused with veratridine, endogenous d-serine release is 10-fold higher than glutamate receptor-evoked release. Release of d-serine from slices does not require internal or external Ca(2+), suggesting a nonvesicular release mechanism. To confirm the neuronal origin of d-serine, we selectively loaded neurons in cortical slices with d-[(3)H]serine or applied d-alanine, which specifically releases d-serine from neurons. Depolarization with veratridine promotes d-serine release in vivo monitored by high temporal resolution microdialysis of the striatum. Our data indicate that the neuronal pool of d-serine plays a major role in d-serine dynamics, with implications for the regulation of NMDAR transmission. Rosenberg, D., Kartvelishvily, E., Shleper, M., Klinker, C. M. C., Bowser, M. T., Wolosker, H. Neuronal release of d-serine: a physiological pathway controlling extracellular d-serine concentration.